2020
DOI: 10.1159/000509908
|View full text |Cite
|
Sign up to set email alerts
|

Possible Involvement of the IL-6/JAK2/STAT3 Pathway in the Hypothalamus in Depressive-Like Behavior of Rats Exposed to Chronic Mild Stress

Abstract: <b><i>Introduction:</i></b> The interleukin-6/janus kinase 2/signal transducer and activator of transcription 3 (IL-6/JAK2/STAT3) pathway plays an important role in immune function, but little research has focused on this pathway in depression. We sought to examine the relationship between the IL-6/JAK2/STAT3 pathway and depressive-like behavior. <b><i>Methods:</i></b> Using a chronic mild stress (CMS) paradigm, a total of 36 adult male Sprague-Dawley rats were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…Likewise, the prior study found an enhanced depressed effect following PPA treatment [ 85 ]. According to previous findings, interleukin-6 elevates STAT3 levels and promotes depression by increasing serotonin transporters (SERT) [ 86 , 87 ]. The increased inflammatory cascade suggested by neurochemical analysis of brain homogenate and blood plasma could contribute to the increased inflammatory reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the prior study found an enhanced depressed effect following PPA treatment [ 85 ]. According to previous findings, interleukin-6 elevates STAT3 levels and promotes depression by increasing serotonin transporters (SERT) [ 86 , 87 ]. The increased inflammatory cascade suggested by neurochemical analysis of brain homogenate and blood plasma could contribute to the increased inflammatory reactions.…”
Section: Discussionmentioning
confidence: 99%
“…STAT3, however, plays an important role in a wide range of physiological functions, including neurogenesis, energy homeostasis, hormonal regulation, and synaptic plasticity [ 13 ]. Despite STAT3 expression being well described in various brain systems [ 18 , 19 , 20 , 21 , 22 ], there is little evidence of its expression in the pineal gland and none is placed in context with its function. Our previous work described the circadian rhythms in Stat3 gene expression and endogenous and LPS-induced STAT3 protein phosphorylation in the SCN.…”
Section: Introductionmentioning
confidence: 99%
“…IL-6 is an important inflammatory factor that promotes the phosphorylation of STAT-3 protein through JAK-2 (43). The IL-6/JAK-2/STAT-3 signaling pathway has been reported to be involved in various diseases, including tumors, ulcerative colitis, hyperuricemic nephropathy and chronic mild stress (44)(45)(46)(47). In the present study, IL-6 was used to activate the JAK-2/STAT-3 signaling pathway.…”
Section: Discussionmentioning
confidence: 90%